Care-seeking behavior for neonatal jaundice in rural northern Nigeria - Z. Iliyasu; Z. Farouk; A. Lawal; M.M. Bello; N.S. Nass; M.H. Aliyu (Elsevier, 2020)
Objective: This study determined the predictors of maternal knowledge and health-seeking behavior for neonatal jaundice in rural Kumbotso, northern Nigeria. Study design: Cross-sectional survey. Method: A total of 361 mothers were interviewed using structured questionnaires. Knowledge scores and care-seeking practices were determined. Adjusted odds ratios were generated from logistic regression models. Results: The proportion of respondents with good, fair and poor knowledge of neonatal jaundice were (46.0%, n ​= ​166), (24.1%, n ​= ​87) and (30.0%, n ​= ​108), respectively. Of the 117 mothers with a jaundiced child, (67.5%, n ​= ​79) and (20.5%, n ​= ​24) received treatment from health facilities and traditional healers, respectively, whereas (12.0%, n ​= ​14) resorted to home remedies. Maternal education Adjusted Odds Ratio (AOR) ​= ​2.39; 95% Confidence Interval (CI): 1.16-4.91) (secondary school versus no formal), source of information on neonatal jaundice (AOR ​= ​11.3; 95%CI: 5.84-21.93) (health worker versus 'others'), recent delivery in a health facility (AOR ​= ​1.83; 95%CI: 1.06-3.14) and having a previously jaundiced child (AOR ​= ​5.06; 95%CI: 2.76-9.27) predicted knowledge. Preference for health facility treatment was predicted by a previously jaundiced child (AOR ​= ​10.04; 95%CI: 5.73-17.60), antenatal care (AOR ​= ​2.97; 95%CI: 1.43-6.15) (≥4 versus 0 visits), source of information on neonatal jaundice (AOR ​= ​2.33; 95%CI: 1.30-4.17) (health worker versus 'others'), and maternal ethnicity (AOR ​= ​0.36; 95%CI: 0.14-0.96) (Hausa-Fulani versus 'others'). Conclusion: Maternal knowledge of neonatal jaundice was sub-optimal. Being educated, health facility delivery, having had a jaundiced child, and receiving information from health workers predicted good knowledge. Having a previously jaundiced child, antenatal care, obtaining information from health workers and maternal ethnicity predicted preference for health facility treatment. Policies and programs should be strengthened to focus on prevention, early detection and prompt management of neonatal jaundice.